White Gauze Test: A Novel Technique in Preventing Post-Hepatectomy Bile Leak - Yugasaravanan, K; Affirul, CA; Zamri, Z; Azlanudin, A; Bong, JJ (Soc Editrice Univ, 2024)
Background. Post-hepatectomy bile leak may lead to undesired morbidity. Multiple methods have been employed to identify this leak but can be inconclusive and taxing. This novel white gauze test is a simple and reliable method. Materials and Methods. This is a prospective study performed from January 2010 until March 2011. All open hepatic resection were included. Dry white gauze is compressed onto the transected surface and observed for bile staining. The leaking duct is repaired immediately upon detection. The process is repeated until negative. Drain was removed on postoperative day-5. Post-operative bile leak is defined as: 1. Bilirubin concentration of the drain fluid is 3 times or higher than serum; 2. Presence of intra-abdominal bile collection on imaging and upon drainage; 3. Bile leak demonstrated on postoperative cholangiography. Results. 42 patients were recruited. Seven (16.7%) patients were cirrhotic with Child-Pugh A. White gauze test were positive for intra-operative bile leaks in 29 patients (70%), which were primarily repaired. As a result, there was no postoperative bile leak in this series. One mortality was detected in this series due to postoperative pancreatic fistula and multi organ failure. Conclusion. The White Gauze Test is a useful method for the prevention of bile leakage after hepatic resection. It is safe, quick and cheap.